Affective Factors: Motivation in Second Language Acquisition, Case of Uzbek Learner - Aminov Farrux Komiljon ugli (Genius Journals, 2022)
The article gives an overview of various learning affective factors in second language acquisition, particularly focusing on motivation and represents some data about one of the Uzbek learner’s cases with research method and findings.
Keywords: Motivation; Language; Acquisition; Affective Factor